Change – The transformative power of citizen science - Katrin Vohland; Daniel Dörler; Florian Heigl; Maria Aristeidou; Eglė Butkevičienė; Claudia Göbel; Mordechai Haklay; Olivia Höhener; Barbara Kieslinger; Andrzej Klimczuk; Gitte Kragh; Moritz Müller; et al. (Pensoft, 2024)
We are in a time of rapid change on multiple levels. Change can be seen as positive by one group and negative by another. As a result, different perspectives on any given change can draw completely different conclusions. In these proceedings we want to address different approaches to change from all kinds of perspectives within the realm of citizen science and participatory research. We discuss both active, transformative change, and the observation of change monitored by citizen science in all kinds of disciplines. We highlight the potential of citizen science to be a change maker in research and society, and as a tool to manage the change happening around us. The proceedings "Change - The transformative power of citizen science" showcase a selection of topics that have been presented and discussed at the ECSA/ACSC 2024 double conference in Vienna and highlight the transformative power, citizen science can have.
Keywords: O35; O36; H43; Z18; Z13; 330; open science; funding; innovation; citizen science; social change; evaluation; societal challenges; public engagement; community resilience; participatory methods; public policies; impact assessment